Electrically stimulated 3D bioprinting of gelatin-polypyrrole hydrogel with dynamic semi-IPN network induces osteogenesis via collective signaling and immunopolarization. (March 2023) - Dutta, Sayan Deb; Ganguly, Keya; Randhawa, Aayushi; Patil, Tejal V.; Patel, Dinesh K.; Lim, Ki-Taek
Abstract: In recent years, three-dimensional (3D) bioprinting of conductive hydrogels has made significant progress in the fabrication of high-resolution biomimetic structures with gradual complexity. However, the lack of an effective cross-linking strategy, ideal shear-thinning, appropriate yield strength, and higher print fidelity with excellent biofunctionality remains a challenge for developing cell-laden constructs, hindering the progress of extrusion-based 3D printing of conductive polymers. In this study, a highly stable and conductive bioink was developed based on polypyrrole-grafted gelatin methacryloyl (GelMA-PPy) with a triple cross-linking (thermo-photo-ionically) strategy for direct ink writing-based 3D printing applications. The triple-cross-linked hydrogel with dynamic semi-inner penetrating polymer network (semi-IPN) displayed excellent shear-thinning properties, with improved shape fidelity and structural stability during 3D printing. The as-fabricated hydrogel ink also exhibited "plug-like non-Newtonian " flow behavior with minimal disturbance. The bioprinted GelMA-PPy-Fe hydrogel showed higher cytocompatibility (93%) of human bone mesenchymal stem cells (hBMSCs) under microcurrent stimulation (250 mV/20 min/day). Moreover, the self-supporting and tunable mechanical properties of the GelMA-PPy bioink allowed 3D printing of high-resolution biological architectures. As a proof of concept, we printed a full-thickness rat bone model to demonstrate the structural stability. Transcriptomic analysis revealed that the 3D bioprinted hBMSCs highly expressed gene hallmarks for NOTCH /mitogen-activated protein kinase ( MAPK )/ SMAD signaling while down-regulating the Wnt / β -Catenin and epigenetic signaling pathways during osteogenic differentiation for up to 7 days. These results suggest that the developed GelMA-PPy bioink is highly stable and non-toxic to hBMSCs and can serve as a promising platform for bone tissue engineering applications.